MicroRNAs Expression Profiles in Cardiovascular Diseases. (12th June 2014) - Bronze-da-Rocha, Elsa
Abstract : The current search for new markers of cardiovascular diseases (CVDs) is explained by the high morbidity and mortality still observed in developed and developing countries due to cardiovascular events. Recently, microRNAs (miRNAs or miRs) have emerged as potential new biomarkers and are small sequences of RNAs that regulate gene expression at posttranscriptional level by inhibiting translation or inducing degradation of the target mRNAs. Circulating miRNAs are involved in the regulation of signaling pathways associated to aging and can be used as novel diagnostic markers for acute and chronic diseases such as cardiovascular pathologies. This review summarizes the biogenesis, maturation, and stability of miRNAs and their use as potential biomarkers for coronary artery disease (CAD), myocardial infarction (MI), and heart failure (HF).